Pancasila Perspective on the Concept of Land Ethic, Deep Ecology, Dark Ecology, and Ecofeminism - Yuwono, Ardi Tri; De, Tung Ming; Flores, Joan Vega; Kai, Leong Jun (Badan Pembinaan Ideologi Pancasila, 2026)
Deforestation and oil palm expansion in Sumatra and Kalimantan through 2025 represent a multidimensional ecological crisis demanding a contextual ethical response. This issue encompasses social, economic, and cultural dimensions, leading to agrarian conflict, biodiversity loss, and high carbon emissions. This research aims to: (1) Identify convergences and dissonances between four global environmental ethics paradigms (Land Ethic, Deep Ecology, Dark Ecology, and Ecofeminism) and Pancasila values; (2) Construct a coherent framework of Pancasila-based Environmental Ethics, and; (3) Formulate policy implications for forest and plantation governance in Indonesia. Using qualitative philosophical-literature study and critical content analysis, the findings yield a synthesis grounded in four main pillars: (1) Communal-Relational, framing nature as part of a broader moral community; (2) Spiritual-Divine, affirming nature’s intrinsic value as creation; (3) Complex Network-Aware, acknowledging and managing paradoxes within global systems, and; (4) Anti-Patriarchal and Corporate Domination and Gender Justice, rejecting the dual oppression of women and nature. The framework offers a holistic normative foundation for reforming forest governance in Indonesia and beyond, emphasizing ecological justice, spirituality, global network transparency, and gender equality.